A convex windowless extrapolation chamber to measure surface dose rate from 106Ru/106Rh episcleral plaques. Issue 5 (30th March 2019) - Hansen, Jon B.; Culberson, Wesley S.; DeWerd, Larry A.
Abstract : Purpose: A convex windowless extrapolation chamber was developed as a primary measurement device to determine surface dose rate from curved 106 Ru/ 106 Rh episcleral plaques. Methods: A convex extrapolation chamber without an entrance window was constructed for this work, and surface dose rate measurements were performed with two curved CCB‐type 106 Ru/ 106 Rh plaques (S/N 2545 and 2596) manufactured by Eckert & Ziegler BEBIG. FARO ® Gage measurements were performed to verify the radius of curvature for the convex electrode and the concave plaque surface. Furthermore, the collecting electrode area was verified through capacitance measurements. Chamber correction factors for divergence and backscatter were generated using the EGSnrc cavity user code. For each source, surface dose rate was measured with the convex extrapolation chamber and compared with on‐contact measurements made with curved un‐laminated EBT3 film strips. A Monte Carlo correction was generated for radiochromic film measurements to account for volume averaging within the active layer and effects of phantom scatter. Additionally, extrapolation chamber results for each plaque were compared with scintillation detector measurements performed by the manufacturer. For the second source (S/N 2596), a comparison was also made with the Monte Carlo‐corrected surface dose rate measured at the National Physical Laboratory (NPL) using cylindrical alanine pellets. Finally, source measurements were performed using conventional ionization chambers (Exradin A26, A1SL, and A20) within a custom fixture to investigate the transfer of extrapolation chamber surface dose rate to clinics. Results: For the first 106 Ru/ 106 Rh plaque (S/N 2545), average surface dose rate from the convex windowless extrapolation chamber was found to be 1.5% higher than the corresponding value from curved un‐laminated EBT3 film measurements and 5.6% lower than the manufacturer value. For the second source (S/N 2596), the extrapolation chamber surface dose rate was 2.5% higher than the un‐laminated EBT3 film result, 4.5% lower than the manufacturer value, and 3.9% higher compared to corrected alanine measurements made at NPL. Total uncertainty in the extrapolation chamber measurement was estimated to be approximately  ± 7.0% ( k  = 2). For the plaque measurements made using conventional ionization chambers with a custom fixture, surface dose rate from the transfer technique was found to agree within 3.8% with the expected convex extrapolation chamber result for S/N 2596. Conclusions: A convex windowless extrapolation chamber was developed as a primary measurement device for 106 Ru/ 106 Rh plaques. Through comparison with the extrapolation chamber, the accuracy of surface dose rate measurements from current dosimetry techniques was assessed and agreement was seen within 5.6%. Finally, it was found that conventional ionization chambers could be calibrated with a reference 106 Ru/ 106 Rh plaque in order to transfer the extrapolation chamber result for surface dose rate to clinics.